Current challenges in postharvest biology of fruit ripening. - PECH, J. C. (2013)
This paper reviews the recent advances in the understanding of the fruit ripening process and describes future challenges. Fruit ripening is a complex developmental process which is orchestrated by the expression of ripening-related genes under the control of a network of signaling pathways. In climacteric fruit components responsible for the production of climacteric ethylene have been identified. Less progress has been made on non-climacteric fruit. Great advances have been made in the characterization of transcription factors (ERFs, RIN, etc?) that induce gene expression through the binding to their promoters. Genetic resources, genome sequencing and ?omics? tools have been developed bringing a huge amount of data that will help to draw together an integrative network of regulatory and signaling pathways responsible for triggering and coordinating the ripening process. The discovery that some ripening events are controlled at the epigenetic level and, not in relation with the DNA sequences, opens novel perspectives.